Literatur Review: Akuntabilitas Pemerintahan Desa Dalam Pengelolaan Dana Desa - Dinda Aulia Safiri (Jurnal Riset Akuntansi, 2023)
This study aims to determine the accountability of village government in managing village funds. The methodology used in this research is Systematic Literature Review (SLR). The data source used in this study was taken from the Google Scholar publication database with the keywords accountability, village government and village management. Based on the review of the journal, it can be concluded that village government accountability in managing village funds has transparent and accountable principles in carrying out the planning, management and accountability stages of village fund allocation (ADD). It is hoped that this research review can become additional information in the field of accounting.